The mechanism-based toxicity screening of particles with use in the food and nutrition sector via the ToxTracker reporter system. (December 2019) - Brown, David M.; Danielsen, Pernille Høgh; Derr, Remco; Moelijker, Nynke; Fowler, Paul; Stone, Vicki; Hendriks, Giel; Møller, Peter; Kermanizadeh, Ali
Abstract: The rapid expansion of the incorporation of nano-sized materials in consumer products overlaps with the necessity for high-throughput reliable screening tools for the identification of the potential hazardous properties of the nanomaterials. The ToxTracker assay (mechanism-based reporter assay based on embryonic stem cells that uses GFP-tagged biomarkers for detection of DNA damage, oxidative stress and general cellular stress) is one such tool, which could prove useful in the field of particle toxicology allowing for high throughput screening. Here, ToxTracker was utilised to evaluate the potential hazardous properties of two particulates currently used in the food industry (vegetable carbon (E153) and food-grade TiO2 (E171)). Due to the fact that ToxTracker is based on a stem cell format, it is crucial that the data generated is assessed for its suitability and comparability to more conventionally used relevant source of cells - in this case cells from the gastrointestinal tract and the liver. Therefore, the cell reporter findings were compared to data from traditional assays (cytotoxicity, anti-oxidant depletion and DNA damage) and tissue relevant cell types. The data showed E171 to be the most cytotoxic, decreased intracellular glutathione and the most significant with regards to genotoxic effects. The ToxTracker data showed comparability to conventional toxicity and oxidative stress assays; however, some discrepancies were evident between the findings from ToxTracker and the comet assay. Highlights: ToxTracker system useful tool in particle toxicology as it uses a 96-well plate format allowing for high throughput screening ToxTracker data showed very good comparability to conventional toxicity and oxidative stress assays Discrepancies were noted for the genotoxicity between ToxTracker and the comet assay Food grade TiO2 was cytotoxic, decreased intracellular glutathione and the most significant for genotoxicity to stem cells, Caco-2 and HepG2 cells